Peningkatan Hasil Belajar IPAS Melalui Penerapan Model Pembelajaran Problem Based Learning di Madrasah Ibtidaiyah - Nisa, Khoirun; Iman, Muis Sad; Nugroho, Irham (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The suboptimal science learning outcomes can be attributed to the inadequate utilisation of pedagogical models by educators, which fail to align with the specific content being taught. In the current educational paradigm, where learning remains predominantly teacher-centered, students are not afforded ample opportunities for active engagement in the learning process. The objective of this study was to investigate the utilisation of the problem-based learning model as a means to enhance science learning results. The research employed the Classroom Action Research (PTK) technique, with the research participants consisting of children from the fourth grade at MI Muhammadiyah Krendetan during the academic year of 2022/2023. The study was conducted in two iterations, employing a research cycle design based on the Kurt Lewin model. This model encompassed four distinct stages: preparation, activity, observation, and reflection. The findings of the research indicate that the use of problem-based learning methodologies in the field of science exhibits a positive impact on students' academic achievements. The aforementioned phenomenon is evident in the activities of the initial phase, wherein the level of student learning attainment stands at 73%, accompanied by a class average of 72.5. In contrast, during cycle II, the rate of student learning completion stood at 87%, accompanied with an average student score of 87.32.